Children's Experiences of Bullying Victimization and the Influence on Their Subjective Well‐Being: A Multinational Comparison. Issue 2 (12th September 2018) - Savahl, Shazly; Montserrat, Carme; Casas, Ferran; Adams, Sabirah; Tiliouine, Habib; Benninger, Elizabeth; Jackson, Kyle
Abstract : The study used data from the second wave of the Children's Worlds Survey to explore the relation between children's experiences of bullying victimization (physical and psychological) and their subjective well‐being (SWB) across three age groups (8, 10, and 12) and 15 global geographical regions. The sample consists of 47, 029 children randomly selected from 15 countries. Data were analyzed using structural equation modeling and multigroup confirmatory factor analysis. The results show appropriate fit structure for the overall model, and that the combined influence of physical and psychological bullying made a significant contribution to SWB across age groups and geographical regions. The findings are interpreted using Cummins's (1995) Homeostasis Theory of SWB. Abstract : The title for this Special Section isChildren's Subjective Well‐Being, edited by Ferran Casas